2017
DOI: 10.18632/oncotarget.18507
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of MALAT1 expression inhibits HUVEC proliferation by upregulation of miR-320a and downregulation of FOXM1 expression

Abstract: Regulation of cancer angiogenesis could be a useful strategy in cancer therapy. Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a long non-coding RNA (lncRNA), and can induce cancer cell proliferation, while lncRNAs, generally are able to act as microRNA (miRNA) sponges. The latter is a type of competitive endogenous RNA (ceRNA) that regulates expression of the targeting miRNAs and protein-coding genes. This study investigated the proliferative role of MALAT1 in human umbilical vein endothel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 34 publications
1
21
0
Order By: Relevance
“…MiR-30b regulates transforming growth factor-β2 expression to influence the ability of HUVECS to form tubes in vitro (29). MiR-98 inhibits low-density lipoprotein (LDL)-induced vascular endothelial cell injury by targeting lectin-like oxidized LDL receptor-1 gene expression (30), while miR-320a overexpression promotes the proliferation of vascular endothelial cells (31). In the present study, it was determined that miR-199a-3p downregulation in patients with T2DM was associated with diabetic angiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-30b regulates transforming growth factor-β2 expression to influence the ability of HUVECS to form tubes in vitro (29). MiR-98 inhibits low-density lipoprotein (LDL)-induced vascular endothelial cell injury by targeting lectin-like oxidized LDL receptor-1 gene expression (30), while miR-320a overexpression promotes the proliferation of vascular endothelial cells (31). In the present study, it was determined that miR-199a-3p downregulation in patients with T2DM was associated with diabetic angiopathy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, MALAT1 also protected HCAECs against ox‐LDL induced apoptosis via sponging miR‐155 targeting suppressor of cytokine‐signaling‐1 (SOCS1) . In contrast, MALAT1 was found to promote the apoptosis of cardiomyocytes line HL‐1 or H9C2 under the H/R condition via sponging miR‐145a, miR‐144, or miR‐320 . MALAT1 promoted hypoxia‐induced apoptosis of myocardial cells by sponging miR‐200a‐3p, which targeted programmed cell death 4 (PDCD4) …”
Section: Malat1 and Pathophysiology Of Cvdsmentioning
confidence: 99%
“…MiRNAs are one of the main regulators of gene transcription, and previous studies have already shown that FOXM1 expression can be regulated by miR-320a [36,37]. To determine if HGK regulates FOXM1 expression by regulating miR-320a, real-time RT-PCR was used to analyze miR-320a expression in HGK-treated Huh7 and HepG2 cells.…”
Section: Hgk Inhibits Foxm1 Expression By Inducing Mir-320a Expressionmentioning
confidence: 99%